First Girgensohnine Analogs Prepared Through InCl3-catalyzed Strecker Reaction and their Bioprospection (2013)
An efficient preparation of the girgensohnine and its close analogs with α-aminonitrile structure, and their spectral characterization were reported for the first time. The piperidine α-aminonitriles were obtained through 5 mol% InCl3-catalyzed one-pot Strecker reaction and tested for antioxidant activity and AChE inhibitory properties. It was found that girgensohnine possesses a moderate AChE inhibitory property while its spiroanalog shows good antioxidant capacity